A Study on the Voltage Control Method of Primary Feeder by the Energy Storage System and Step Voltage Regulator. Issue 4 (2019) - Kim, Byungki; Ryu, Kyung-Sang; Kim, Dae-Jin; Nam, Yang-Hyun; Ko, Heesang; Kim, Ho-Chan
Abstract: In order to keep the customer voltages within nominal voltage boundary (220±6%), operation method of SVR(Step Voltage Regulator) at primary feeder is very important considering the scheduled tap time delay(120 sec) of SVR However, the compensation of voltage during the tap delay time of SVR is being required at primary feeder introduced in RES (Renewable Energy Recourse). Because customer voltage should be to exceed nominal voltage boundary during the operated time of RES. Therefore, in order to keep the secondary feeder voltage within nominal voltage boundary at all the time, this paper proposed the voltage control method in primary feeder by using coordination control algorithm between ESS (Energy Storage System) and SVR. From the simulation results analysis of customer voltages by presenting voltage control method between ESS and SVR based on the PSCAD/EMTDC, it is confirmed that customer voltage in distribution system can be maintained within allowable limit.